Implant Material, Type of Fixation at the Shaft, and Position of Plate Modify Biomechanics of Distal Femur Plate Osteosynthesis. Issue 8 (August 2017) - Kandemir, Utku; Augat, Peter; Konowalczyk, Stefanie; Wipf, Felix; von Oldenburg, Geert; Schmidt, Ulf
Abstract : Objectives: To investigate whether (1) the type of fixation at the shaft (hybrid vs. locking), (2) the position of the plate (offset vs. contact) and (3) the implant material has a significant effect on (a) construct stiffness and (b) fatigue life in a distal femur extraarticular comminuted fracture model using the same design of distal femur periarticular locking plate. Methods: An extraarticular severely comminuted distal femoral fracture pattern (OTA/AO 33-A3) was simulated using artificial bone substitutes. Ten-hole distal lateral femur locking plates were used for fixation per the recommended surgical technique. At the distal metaphyseal fragment, all possible locking screws were placed. For the proximal diaphyseal fragment, different types of screws were used to create 4 different fixation constructs: (1) stainless steel hybrid (SSH), (2) stainless steel locked (SSL), (3) titanium locked (TiL), and (4) stainless steel locked with 5-mm offset at the diaphysis (SSLO). Six specimens of each construct configuration were tested. First, each specimen was nondestructively loaded axially to determine the stiffness. Then, each specimen was cyclically loaded with increasing load levels until failure. Results: Construct Stiffness: The fixation construct with a stainless steel plate and hybrid fixation (SSH) had the highest stiffness followed by the construct with a stainless steel plate and locking screws (SSL) and were not statistically different from each other. Offset placement (SSLO) and using a titanium implant (TiL) significantly reduced construct stiffness. Fatigue Failure: The stainless steel with hybrid fixation group (SSH) withstood the most number of cycles to failure and higher loads, followed by the stainless steel plate and locking screw group (SSL), stainless steel plate with locking screws and offset group (SSLO), and the titanium plate and locking screws group (TiL) consecutively. Offset placement (SSLO) as well as using a titanium implant (TiL) reduced cycles to failure. Conclusions: Using the same plate design, the study showed that implant material, screw type, and position of the plate affect the construct stiffness and fatigue life of the fixation construct. With this knowledge, the surgeon can decide the optimal construct based on a given fracture pattern, bone strength, and reduction quality. Abstract : Supplemental Digital Content is Available in the Text.